Groundnut Policies, Global Trade Dynamics, and the Impact of Trade Liberalization - Diop, Ndiame; Beghin, John; Sewadeh, Mirvat (World Bank, Washington, D.C., 2013)
Groundnut products are of central economic importance to millions of smallholders in Africa, India, and Southern China. The products generate 60 percent of rural cash income and account for about 70 percent of the rural labor force in Senegal and The Gambia. Groundnut trade is heavily distorted, and this has affected the competitive position of various players in world markets. Using a partial-equilibrium, multi-market, international model, the authors analyze the trade and welfare effects of several groundnut trade liberalization scenarios compared with the recent historical baseline. They evaluate net welfare as the sum of consumers' equivalent variation, quasi-profits in farming, quasi-profits in crushing, and taxpayers' revenues and outlays implied by distortions. The authors find that trade liberalization in groundnut markets has a strong South-South dimension with policies in India, and to a lesser extent China, heavily depressing the world prices of groundnut products at the expense of smaller developing countries mainly located in Africa. Under free trade, African exporters would gain because they are net sellers of groundnut products. In India, consumers would be better off with lower consumer prices resulting from the removal of prohibitive tariffs and large imports of groundnut products. The cost of adjustment would fall on Indian farmers and crushers. In China, crush margins would improve because of the large terms of trade effects in the groundnut oil market relative to the seed market. China's groundnut product exports would expand dramatically. Net buyers of groundnut products in OECD countries would be worse off. The authors draw implications for the Doha negotiations.